The Impact of Flipped Learning Strategy on Enhancing the Motivation for Learning and Achievement among Students of Al-Hosun University College - Alswalha, Ali Suliman; Al Homran, Mohmad Khalid; Eyadat , Hitham Mustafa (Dirasat: Educational Sciences, 2020)
This study aimed at discovering the effect of using flipped learning strategy on enhancing the motivation for learning and achievement among students of Al-Hosun University College. The study followed a semi-empirical approach. The sample of the study comprised (41) students who enrolled in Instructional Design course in Al- Hosun University in the academic year (2017/2018). The study sample was divided into two groups: an experimental group which consisted of (23) students and a control group which consisted of (18) students. The researchers built a motivation learning scale and achievement exam. The results of the study showed a statistically significant difference between the mean scores of the experimental groups who studied using the Flipped Learning Strategy and the control group scores that were taught in the traditional way on the motivation scale. Hence, the study recommends using flipped learning strategy in teaching at universities.